The Effect of Aromatherapy on Anxiety in Patients Undergoing Hemodialysis during COVID-19 Pandemic - Setyawan, Aris; Syahruramdhani, Syahruramdhani; Setyaningrum, Niken (Universitas Aisyah Pringsewu, 2022)
The COVID-19 pandemic causes psychological issues such as anxiety, particularly in kidney failure patients who must undergo hemodialysis. Aromatherapy Lavender could be used to help patients overcome anxiety. The purpose of this study was to see how lavender aromatherapy affected the anxiety of patients undergoing hemodialysis during the COVID-19 pandemic. The research design of this study was a quasi-experimental with a pre-post-test control group. A simple random sampling technique was used to select 32 patients as respondents. The Zung-Self Rating Anxiety Scale is used by the instrument (ZSAS). The parametric t-Test test was used to analyze the data. The study's findings revealed a significant decrease in the intervention group's pre-post value, with a p-value of 0.001. The delta value of the control and intervention groups differed significantly, with a p-value of 0.001. During the pandemic, lavender aromatherapy is effective in reducing anxiety of hemodialysis patients. Nurses can use aromatherapy lavender as a complementary therapy to help patients undergoing hemodialysis overcome their anxiety Abstrak: Pandemi COVID-19 menyebabkan masalah psikologis seperti kecemasan, terutama pada pasien gagal ginjal yang harus menjalani hemodialisis. Aromaterapi Lavender dapat digunakan untuk membantu pasien mengatasi kecemasan. Tujuan dari penelitian ini adalah untuk melihat bagaimana aromaterapi lavender mempengaruhi kecemasan pasien yang menjalani hemodialisis selama pandemi COVID-19. Desain penelitian penelitian ini adalah eksperimen semu dengan pre-post-test control group. Teknik simple random sampling digunakan untuk memilih 32 pasien sebagai responden. Skala Kecemasan Peringkat Zung-Self digunakan oleh instrumen (ZSAS). Uji parametrik t-Test digunakan untuk menganalisis data. Temuan penelitian mengungkapkan penurunan yang signifikan dalam nilai pra-pasca kelompok intervensi, dengan nilai p 0,001. Nilai delta kelompok kontrol dan intervensi berbeda secara signifikan, dengan p-value 0,001. Di masa pandemi, aromaterapi lavender efektif mengurangi kecemasan pasien hemodialisis. Perawat dapat menggunakan aromaterapi lavender sebagai terapi komplementer untuk membantu pasien yang menjalani hemodialisis mengatasi kecemasannya.